MOTIF KETERBUKAAN KELOMPOK MINORITAS LGBT (LESBIAN, GAY, BISEKSUAL, DAN TRANSGENDER) DI SURABAYA PADA MEDIA SOSIAL TIKTOK (The Commercium, 2023)
Social media has become a part and even a necessity in people's daily lives, this allows them to shareinformation or even communicate with each other. The freedom to use the Tiktok social media application allows anyone to use it, including the LGBT minority group. LGBT groups often receive rejection in society because LGBT are considered a group that deviates and is not in accordance with the norms, culture and religious teachings that exist in Indonesia. The LGBT group, which so far has only been silent and has not dared to speak out regarding their views for fear of isolation and pressure from society, now they have the courage to show openness to the currently popular social media, namely the social media Tiktok. This study aims to determine the openness motives of LGBT minority groups in disclosing social media Tiktok with Alfred Schutz's phenomenological theory, namely by using the because of motive and also the purpose motive (in order to motive). This is done by exploring views and experiences. individuals from the LGBT community in Surabaya who actively use the Tiktok platform.This study used a qualitative approach with the phenomenological method, the types of data used were primary data and secondary data, the data collection techniques used were interviews, observation and documentation, the data analysis techniques used descriptive qualitative and data validity techniques using source triangulation and researcher participation.The results of this study are that the LGBT group in Surabaya has a motive for being open to social media Tiktok because they have awareness of sexual orientation, receive rejection in the social environment, have accepted reality and have standards openness. In addition, the goal motive is to find a partner, add friendship, answer every question as a means of entertainment, show self-existence and want to be yourself. Although in the end they will receive criticism and negative comments on Tiktok social media, for LGBT people voicing their views is important thing.